Anorexia nervosa, neuroimaging research, and the contextual salience of food cues: The food approach–avoidance conundrum. Issue 8 (30th May 2018) - Murray, Stuart B.; Strigo, Irina A.
Abstract: Anorexia nervosa (AN) is characterized by an avoidance and marked apprehension around food intake, yet paradoxically, those with AN often display approach behaviors to food, engaging in food shopping or preparation activities which are described as rewarding. This approach–avoidance conundrum is of much importance as neuroimaging studies continue to probe mechanisms relating to core AN psychopathology. This Idea Worth Researching discusses the notion that neuroimaging studies relying on food cue presentation paradigms may be methodologically flawed without specifying the contextual salience of the food cues presented in paradigms. The appraisal of food cues may diverge as a function of one's intent‐to‐eat, and thus, neuroimaging studies not specifying the contextual salience of food cues (i.e., intent‐to‐eat or not) may confound two distinctly different processes.